The Influence of Leadership and Motivation on Teacher Job Satisfaction at SMA Brigjend Katamso II Medan - Winda Sihotang; Ibnu Hajar; Aman Simaremare; Agustina Muliati; Rini Ade Octaviany (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the effect of principal leadership and teacher work motivation on teacher satisfaction. Teacher satisfaction has a very important position in the context of improving and controlling the quality of education. This type of research is quantitative. Data was obtained by survey method, namely by distributing questionnaires as research instruments. This research was conducted at Brigjend Katamso II Senior High School Medan, Indonesia. The research sample was 49 teachers. Analysis of the data using correlational analysis techniques and multiple regression. This research is an ex-post facto research, because the researcher does not manipulate the existing variables and directly looks for the existence and level of the relationship between variables which is reflected in the correlation coefficient. The results of the study concluded: (1) there was a significant influence of principal's leadership on teacher satisfaction; (2) there is an effect of teacher work motivation on teacher satisfaction; and (3) there is a joint effect of principal's leadership and teacher's work motivation on teacher satisfaction.